Randomized controlled three-arm study of NADA acupuncture for alcohol addiction - Krause, Florian; Penzlin, Ana Isabel; Ritschel, Gerhard; Barlinn, Kristian; Reichmann, Heinz; Weidner, Kerstin; Siepmann, Martin; Siepmann, Timo (Addictive behaviors, 2020)
•NADA acupuncture improved cardiac autonomic function in patients with alcohol addiction.•The treatment was not able to modulate craving or abstinence.•The long term effects of NADA acupuncture on cardiovascular health in patients with alcohol addiction warrant investigation. Alcohol addiction compromises cardiovascular health, possibly due to impaired control of the heart and vasculature by the autonomic nervous system. We aimed to assess the effects of National Acupuncture Detoxification Association (NADA) acupuncture on cardiovascular autonomic functions, psychiatric comorbidities and abstinence in patients addicted to alcohol. A randomized sham controlled three-arm study was undertaken in 72 patients (nine females, aged 43.7 ± 9.2 years, mean ± SD) undergoing in-patient rehabilitation for alcohol addiction. Patients were randomly allocated (1:1:1) to receive twenty 30-minute NADA or sham acupuncture sessions within six weeks or no intervention. They were evaluated for craving, depression, anxiety and autonomic control of the heart (heart rate variability, HRV), vasculature (laser Doppler flowmetry) and sweat glands (sympathetic skin response). Testing was performed at baseline, immediately post intervention (sham intervention or control period, respectively) and another four weeks later. Abstinence was assessed one year after study completion. Patients in the NADA arm displayed increased HRV immediately post-intervention compared to baseline (SDNN: 72.8 ms ± 34.2 ms vs. 57.9 ms ± 31.2 ms, p = 0.001). This increase was sustained four weeks later (66.2 ms ± 32.4 ms, p = 0.015). HRV remained unaltered following sham or no acupuncture (p = n.s.). Autonomic function of vasculature and sweat glands, psychiatric comorbidities and one-year abstinence did not differ between study arms. NADA acupuncture may improve autonomic cardiac function. However, this improvement appears not to translate into alleviation of psychiatric comorbidities or sustained abstinence.